2016
DOI: 10.4186/ej.2016.20.3.63
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Different Al-based Solid Acid Catalysts for Catalytic Dehydration of Ethanol

Abstract: Abstract. In this present study, the catalytic dehydration of ethanol over three different Al-based solid acid catalysts including H-beta zeolite (HBZ), modified H-beta zeolite with γ-Al2O3 (Al-HBZ) and mixed γ-χ phase of Al2O3 (M-Al) catalysts was investigated. The ethanol dehydration reaction was performed at temperature range of 200 to 400 o C. It revealed that all catalysts exhibited higher ethanol conversion with increased temperatures. At low temperatures (ca. 200 to 250 o C), diethyl ether (DEE) was obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 28 publications
(36 reference statements)
0
12
0
Order By: Relevance
“…Finally, the feed and product compositions at reactor effluent were detected by using Shimadzu gas chromatography (GC 8A) with flame ionization detector (FID) using DB-5 capillary column. The reaction testing system was also demonstrated by Kamsuwan and Jongsomjit 27) .…”
Section: Ethanol Dehydration Reactionmentioning
confidence: 92%
“…Finally, the feed and product compositions at reactor effluent were detected by using Shimadzu gas chromatography (GC 8A) with flame ionization detector (FID) using DB-5 capillary column. The reaction testing system was also demonstrated by Kamsuwan and Jongsomjit 27) .…”
Section: Ethanol Dehydration Reactionmentioning
confidence: 92%
“…Moreover, the ability of H-ZSM-5 to catalyze the dehydration of ethanol to ethylene at low temperatures (200–300 °C) has made it commercially valuable and promising for further improvement in its efficiency. ZSM-5 zeolite catalysts treated by dealumination or desilication and modified with phosphorous or lanthanum have been reported. For example, Xin et al (2014) post-treated ZSM-5 zeolite powder by desilication with sodium hydroxide, dealumination with oxalic acid, or both in a sequential way to finely tune zeolite catalysts in a hierarchical porous structure with varying acidities Table summarizes the ability of catalysts to dehydrate ethanol to ethylene.…”
Section: Introductionmentioning
confidence: 99%
“…As seen in Table 3, it indicated that the TiO 2 -SG exhibited lower amount of acid site than the TiO 2 -SV. However, with tungsten loading on both supports, it showed signi cant increase in weak and total acid sites for both WO 3 /TiO 2 -SG and WO 3 /TiO 2 -SV catalysts, which is necessary for enhancing the production of ethylene and DEE [38,39]. In addition, it can be observed that the WO 3 /TiO 2 -SV catalyst exhibited the highest amount of total acid sites at 3645 µmol/g cat.…”
Section: International Journal Of Chemical Engineeringmentioning
confidence: 93%